Analysis of the Readiness of Purbalingga Regency SMEs in Adopting Cloud Based Accounting - Nugroho Budi Wirawan; Puji Lestari; Agung Praptapa; Eliada Herwiyanti (Citakonsultindo, 2024)
The aim of this research is to analyze the influence of top management support on perceived usefulness, analyze the influence of top management support on perceived ease of use, analyze the influence of technological capabilities on perceived usefulness, analyze the influence of technological capabilities on perceived ease of use, analyze the influence of ecosystem capabilities on perceived usefulness, analyzing the influence of ecosystem capabilities on perceived ease of use, analyzing the influence of perceived usefulness on intention to use cloud based accounting, analyzing the influence of perceived ease of use on intention to use cloud based accounting, analyzing the influence of intention to use cloud based accounting cloud based accounting adoption. The type of this research is quantitative, data was collected using a survey method involving respondents from SMEs in the Purbalingga Regency area. The population in this research is SMEs in the Purbalingga Regency area to dig deeper into the factors that influence the adoption of cloud based accounting in SMEs. The number of SMEs in Purbalingga Regency is 98,967, using the Slovin formula the sample size is 100. Partial Least Square (PLS) model analysis was used in this research. The results of this research are that top management support has no significant effect on perceived usefulness, top management support has no significant effect on perceived ease of use, support of technological capabilities has no significant effect on perceived usefulness, support of technological capabilities has a significant effect on perceived ease of use, support of ecosystem capabilities significant effect on perceived usefulness, ecosystem capability support has a significant effect on perceived ease of use, perceived usefulness has no significant effect on intention to use cloud based accounting, perceived ease of use has a significant effect on intention to use cloud based accounting, and intention to use cloud based accounting has a significant effect on cloud based accounting.